1999
DOI: 10.1002/(sici)1097-4652(199902)178:2<188::aid-jcp8>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

1,25 dihydroxyvitamin D3 enhances the calcium response of keratinocytes

Abstract: The steroid hormone 1,25 dihydroxyvitamin D3 (1,25(OH)2D3) regulates cell proliferation and differentiation. Intracellular calcium (Cai) concentrations play a crucial role in these events. From our previous studies, we have demonstrated a calcium receptor (CaR) in keratinocytes which appears to regulate the initial release of Cai from intracellular stores in response to extracellular calcium (Cao) and so is likely to participate in the differentiation process. In this study, we determined whether the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Treatment of keratinocytes with a medium containing high calcium also stimulated keratinocyte differentiation by increasing the expression of involucrin and TGase I. 1,25(OH)2D also promoted keratinocyte differentiation, at least in part by increasing intracellular calcium and by increased expression of calcium receptors in keratinocytes (36). Calcitriol indirectly induces the expression of keratin 1, involucrin, TGase I, loricrin, and filaggrin, which are required for CE formation.…”
Section: Effects Of Vitamin D3 Analogues In Psoriasismentioning
confidence: 99%
“…Treatment of keratinocytes with a medium containing high calcium also stimulated keratinocyte differentiation by increasing the expression of involucrin and TGase I. 1,25(OH)2D also promoted keratinocyte differentiation, at least in part by increasing intracellular calcium and by increased expression of calcium receptors in keratinocytes (36). Calcitriol indirectly induces the expression of keratin 1, involucrin, TGase I, loricrin, and filaggrin, which are required for CE formation.…”
Section: Effects Of Vitamin D3 Analogues In Psoriasismentioning
confidence: 99%
“…4 illustrates points at which 1,25(OH) 2 D interfaces with the calcium signaling system. The expression of the CaR is increased by 1,25(OH) 2 D, making the keratinocyte more sensitive to the prodifferentiating actions of calcium [45]. All of the PLC family members are induced by 1,25(OH) 2 D [46] as they are by calcium [31], and blocking PLC-␥1 expression prevents both 1,25(OH) 2 D and calcium stimulated differentiation [31,47].…”
Section: Cellular Mechanisms For 125(oh) 2 D Actionsmentioning
confidence: 99%
“…How does VD3 modulate IP 3 -dependent Ca 2+ responses? It has been reported that VD3 promotes keratinocyte differentiation by increasing [Ca 2+ ] i via increased expression of phospholipase C (14,20). In addition to this genomic action, VD3 was postulated to act through a membrane-associated receptor to account for the rapid stimulation of Ca 2+ release from intracellular stores and subsequent Ca 2+ entry in skeletal muscle cells (16,19 ] i seems to be associated with similar directional cellular movements.…”
Section: Effect Of Vd3 On Camentioning
confidence: 92%
“…Many of the biological actions of VD3 are mediated by the nuclear vitamin D receptor (VDR), a ligand-dependent transcription factor belonging to the superfamily of steroid/thyroid hormone receptors (13). Moreover, VD3 modulates the intracellular Ca 2+ concentration ([Ca 2+ ] i ) in some cell types (14,16,19,20 …”
mentioning
confidence: 99%